Cause-Effect Relationships between Changes in Compensation and Economic Growth - Przekota, Grzegorz (Journal of Finance and Financial Law, 2023)
The purpose of the article. Compensation for work and economic growth are two economic variables that economists pay particular attention to. Many theories have been developed to link these quantities in cause-and-effect relationships. These theories often differ in determining which of these quantities is the cause and which is the effect. The research carried out in this article examines this relationship. The aim of the paper was to determine the direction and strength of causality in the relationship between wages and economic growth. To test the hypothesis that the relationship between changes in the level of wages and the rate of economic growth is significant and that the direction of this relationship is determined by time lags. Methodology. The research is based on annual data on the share of compensation in GDP and GDP dynamics for OECD countries for the years 2003–2021. Correlation analysis and multilevel modelling are used. Annual averages for the whole group of countries were analysed, as well as correlations between each country’s time series individually and together in a multilevel analysis model. In order to eliminate spurious correlations, the analysis was performed on size increments. Results of the research. It was found that current wage increases have a depressing effect on current eco-nomic growth, while current economic growth has a stimulating effect on future wage increases. Such findings could provide the basis for government programmes aimed at stimulating the economy rather than regulating wages.